SAT0439 Integrated safety summary of tofacitinib in psoriatic arthritis clinical studies. (15th June 2017) - Burmester, G; FitzGerald, O; Winthrop, K; Williams, G; Azevedo, VF; Rigby, WFC; Kanik, K; Wang, C; Biswas, P; Jones, T; Menon, S; Palmetto, N; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor under investigation for psoriatic arthritis (PsA). Objectives: To describe the safety profile of tofacitinib from integrated Phase (P)3 and long-term extension (LTE) studies. Methods: Data were analysed for patients (pts) who received ≥1 dose of tofacitinib 5 or 10 mg BID or placebo (PBO), integrated across 2 P3 studies (OPAL Broaden [12 months; NCT01877668 ]; OPAL Beyond [6 months; NCT01882439 ]) and 1 LTE study (OPAL Balance [ongoing, database not locked; NCT01976364 ]). Common adverse events (AEs; occurring in ≥2% of tofacitinib pts in any group) were analysed in the PBO-controlled portion (Months 0–3) of the P3 studies (Cohort 1 [C1]). Serious AEs (SAEs) and discontinuations due to AEs were analysed over 12 months in pts randomised to tofacitinib 5 or 10 mg BID in P3 studies (Cohort 2a [C2a]); pts randomised to PBO were excluded from this analysis. Deaths and AEs of special interest (serious infections [SI], herpes zoster [HZ], opportunistic infections [OI] including HZ, major adverse cardiac events [MACE], malignancies, non-melanoma skin cancer [NMSC]) were evaluated in all tofacitinib-treated pts in the P3 and LTE studies (Cohort 3 [C3]). Incidence rates (IR; pts with events/100 pt-years [PY] and 95% confidence intervals) are reported. Laboratory results will be reported in future publications. Results: C1 included 474 tofacitinib- and 236 PBO-treated pts; C2a included 474 tofacitinib-treated pts; and C3 included 783 tofacitinib-treated pts (exposure: 776 PY). Nasopharyngitis (5.9%) and headache (8.5%) were the most commonly reported AEs at Month 3 in pts receiving tofacitinib 5 and 10 mg BID, respectively (Table). In pts randomised to tofacitinib 5 or 10 mg BID, over 12 months (C2a), the IRs for SAEs were 7.92 (4.09, 13.84) and 8.11 (4.19, 14.17), respectively. Discontinuation due to AEs occurred in 11 (4.6%) and 11 (4.7%) pts randomised to tofacitinib 5 and 10 mg BID, respectively, with IRs of 7.16 (3.58, 12.82) and 7.31 (3.65, 13.08), respectively, over 12 months (C2a). Across all tofacitinib-treated pts in the P3 and LTE studies (C3), SIs occurred in 11 pts (1.4%; IR 1.40 [0.70, 2.50]). HZ was reported in 16 pts (2.0%; IR 2.05 [1.17, 3.33]) receiving tofacitinib. All 3 cases of multidermatomal HZ were adjudicated as OIs; these were the only OIs (0.4%; IR 0.38 [0.08, 1.11]). In C3, 2 deaths occurred (0.3%; IR 0.25 [0.03, 0.91]); all were considered unrelated to the study drug. MACE were reported in 3 pts (0.4%; IR 0.38 [0.08, 1.11]), malignancies (excluding NMSC) in 5 pts (0.6%; IR 0.63 [0.21, 1.48]) and NMSC in 4 pts (0.5%; IR 0.51 [0.14, 1.30]). Conclusions: Tofacitinib was well tolerated in pts with PsA, with a safety profile consistent to that seen in RA; no new risks were identified. Longer-term follow-up and larger pt populations will provide further information on the safety profile of tofacitinib in pts with PsA. Acknowledgements: These studies were sponsored by Pfizer Inc. Editorial support was provided by C Viegelmann of CMC and was funded by Pfizer Inc. Disclosure of Interest: G. Burmester Grant/research support from: UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Hexal, Janssen, MSD, MedImmune, Novartis, Pfizer Inc, Sanofi, Roche, Speakers bureau: AbbVie, Bristol-Myers Squibb, Hexal, MSD, Novartis, Pfizer Inc, Roche, O. FitzGerald Grant/research support from: AbbVie, Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Eli Lilly, Janssen, Pfizer Inc, Speakers bureau: Celgene, Janssen, Novartis, K. Winthrop Grant/research support from: Bristol-Myers Squibb, Pfizer Inc, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Eli Lilly, Galapagos, Pfizer Inc, UCB, G. Williams Consultant for: Pfizer Inc, V. Azevedo Grant/research support from: Bristol-Myers Squibb, GSK, Pfizer Inc, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Merck Novartis, Pfizer Inc, Serono, W. F. Rigby Grant/research support from: Amgen, Pfizer Inc, Roche, Consultant for: Bristol-Myers Squibb, Eli Lilly, Pfizer Inc, Roche, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, P. Biswas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Jones Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Menon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, N. Palmetto Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Rojo Shareholder of: Pfizer Inc, Employee of: Pfizer Inc